IbM BAGI SANTRI DI KECAMATAN GUNUNGPATI KOTA SEMARANG UNTUK MENINGKATKAN MINAT BERWIRAUSAHA - Kardoyo Kardoyo; Muhsin Muhsin; Fachrurrozie Fachrurrozie; Ahmad Nurkhin (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2018)
Entrepreneurship education has become a very important thing in the present, not least at Islamic boarding schools (pondok pesantren). The form of entrepreneurship education is also diverse. Establishment of minimarket, animal husbandry, plantation and other business units in Islamic boarding schools is a step taken in order to improve entrepreneurial skills. However, the understanding and competence of santri entrepreneurship in Islamic boarding schools still requires strengthening and mentoring from academics and professionals. The target of service is the PP As Salafy Al Asror students who are studying at MA Al Asror, especially the XI and XII classes. The method of carrying out service activities is counseling, practice and mentoring. Extension activities are given to provide a real picture of the intricacies of entrepreneurship. Then proceed with the practice of preparing a business plan and mentoring the preparation of a business plan. The service partner gave a good response to the community services team. The community services activities can be carried out twice with the basic concepts of entrepreneurship and the preparation of a business plan. Participants can participate in activities enthusiastically and are able to produce business ideas contained in business plan documents. The first material presented by lecturer from Faculty of Economics UNNES. Whereas the service team provided intensive assistance in the second stage of community service activities.Key words: entrepreneurship education, Islamic boarding schools, business plan